FUNGSI PENGAWASAN OTORITAS JASA KEUANGAN (OJK) TERKAIT PERLINDUNGAN KONSUMEN PADA LAYANAN PEER TO PEER LANDING FINTECH - Jafar, Ahmad Ridha (IAIN Tulungagung, 2019)
The development of information technology has generated the innovation in the financial technology (fintech). One of the innovation is peer to peer lending system, which targeted the public and small scale business to provide the easily accessed capital. The regulation issued by Bank of Indonesia and the Board of Financial Authority is expected to assure the consumers? safety. The peer to peer lending system has turned out to give positive benefit in accelerating the economic growth. Anyway, the potential leak of the consumers? personal data threaten the sustainability of the fintech industry. Therefore, the prevention and the supervision system must be seriously considered. This study concludes that th fintech still need another set of regulations to protect the consumers, and to optimize the supervision from Bank of Indonesia and the Board of Financial Authority.Keywords: Peer-to-peer lending, financial technology, regulasi